Positive Solution of Boundary Value Problem Involving Fractional Pantograph Differential Equation: Piyachat Borisut, Chaiwat Auipa-arch - Team, Support (Thai Journal of Mathematics, 2020)
In this paper, we study and integrate the positive solution of fractional pantograph differential equation with mixed conditions. By using the fixed point theorems, the main tools for finding positive solutions and uniqueness of this problem are obtained.